Green Techniques for Energy Providing - Agarwal, Renu; Tarar, Nikita (Journal for Research in Applied Sciences and Biotechnology, 2024)
The pressing global challenges of pollution, resource depletion, and climate change. This abstract provides an overview of modern approaches in green chemistry, focusing on key principles and practices that are transforming the way we design, produce, and use chemicals. Several critical keywords are highlighted to better understand the evolving landscape of green chemistry, including sustainable synthesis, renewable feedstocks, catalysis, atom economy, and eco-friendly processes. By adopting these approaches, researchers and industries are striving to minimize the environmental impact of chemical processes and develop innovative solutions to safeguard the planet for future generations. This abstract serves as a primer for exploring the latest developments and trends in green chemistry, offering valuable insights for those committed to sustainable and responsible chemistry practices.